Experimental labor markets and policy considerations: Incomplete contracts and macroeconomic aspects - Fortuna Casoria; Arno Riedl (Institute for the Study of Labor (IZA), 2012)
This survey focuses on experimental labor markets investigating two aspects that deem us important for a better understanding of labor market relations and the consequences for labor market policies. The first part of the survey is dedicated to papers that assess the prevalence of reciprocal considerations in incomplete labor contracts. The second part summarizes the relatively small but growing experimental literature exploring labor issues in a macroeconomics and public finance setting and studying the interaction between taxation and labor market outcomes.
Keywords: C90; C92; C93; D01; D51; E24; E62; F41; J01; J08; 330; laboratory experiment; labor markets; incomplete contracts; gift-exchange; labor market policy; Arbeitsmarktpolitik; Beschäftigungseffekt; Arbeitsmarkt; Unvollkommener Markt; Arbeitsmarkttheorie; Test